Spectral Beam Splitting Technology for Photovoltaic and Concentrating Solar Thermal Hybrid Systems: A Review (Journal of Solar Energy Research Updates, 2020)
As a promising technology, spectral beam splitting (SBS) technology is the research focus currently in photovoltaic and concentrating solar thermal (PV/CST) hybrid systems. Spectral splitting filters can optimally exploit the solar spectrum and reach higher conversion efficiencies of solar energy. In this paper, we provide a review of the recently published research in spectral splitting filters and summary the research details of SBS technology, including the proposed methods, types, materials, performance advantages, technical obstacles of the filters. Moreover, the paper presents the research status of the SBS technology and evaluates the prospects of various filters in PV/CST hybrid systems. This review can help the researchers and practitioners better understand the SBS technology and features of different spectral splitting filters for the PV/CST hybrid system.